2012
DOI: 10.1016/j.jep.2012.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatment with Tong-Luo-San-Jie gel alleviates bone cancer pain in rats

Abstract: Ethnopharmacological relevance The herbal analgesic gel Tong-Luo-San-Jie (TLSJ) and its modifications are used in traditional Chinese medicine to manage cancer pain. However, its mechanisms are still unknown. Aim of the study To investigate the effects and mechanisms of TLSJ gel on bone cancer pain in a rat model. Materials and Methods A bone cancer pain rat model was established by inoculating Walker 256 rat carcinoma cells directly into the right tibial medullary cavity of Sprague-Dawley rats (150–170 g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 42 publications
4
25
0
1
Order By: Relevance
“…TLSJ treatment significantly restored bone cancer-induced decrease of paw withdrawal latency and mechanical threshold compared to inert gel. Meanwhile, it decreased the level of carboxyterminal pyridinoline cross-linked type I collagen telopeptides, bone-specific alkaline phosphatase and inhibited osteoclast activities in blood serum [55]. Furthermore, TLSJ was deemed valid in alleviating bone cancer-induced mechanical allodynia and thermal hyperalgesia by downregulating transient receptor potential channel expression in lumbar dorsal root ganglia and lumbar spinal cord interleukin-17A (IL-17A) in spinal astrocytes [56].…”
Section: Pharmacologymentioning
confidence: 99%
“…TLSJ treatment significantly restored bone cancer-induced decrease of paw withdrawal latency and mechanical threshold compared to inert gel. Meanwhile, it decreased the level of carboxyterminal pyridinoline cross-linked type I collagen telopeptides, bone-specific alkaline phosphatase and inhibited osteoclast activities in blood serum [55]. Furthermore, TLSJ was deemed valid in alleviating bone cancer-induced mechanical allodynia and thermal hyperalgesia by downregulating transient receptor potential channel expression in lumbar dorsal root ganglia and lumbar spinal cord interleukin-17A (IL-17A) in spinal astrocytes [56].…”
Section: Pharmacologymentioning
confidence: 99%
“…18 The active ingredients were extracted and the LTTL gel was prepared as previously described. 10 The chemical profile of the formulated gel was established by ultraperformance liquid chromatography analysis as previously reported. 10 …”
Section: Herbal Preparation and Extractionmentioning
confidence: 99%
“…After 6-7 days, the cells in the ascitic fluid were collected, and resuspended at a concentration of 3.5x10 5 cells/6 µl in phosphate-buffered saline (PBS). The bone cancer pain model was established according to the method previously described (9). In brief, following anesthetization with pentobarbital (50 mg/kg), under aseptic conditions, right lateral superficial incisions were made in the skin covering the patella of rats.…”
Section: Long-term Toxicity Studymentioning
confidence: 99%
“…Confirmed by clinical trials and experimental studies, certain TCMs possess remarkable efficacies in pain treatment, including Tou-Feng-Yu pill (8) and Tong-Luo-San-Jie gel (9). Moreover, surveys have revealed that TCMs are used as important auxiliary therapeutics among 41-62% of cancer patients (9,10).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation